Pathos, singularidade e gramáticas de reconhecimento - efeitos de sujeito no autismo - Romano, Lucas Silva (2021)
The status of suffering in autism calls for a reading of the singular present in the most varied ways of crossing pain in the field of the living. Diluted in the load of meanings that bear the signifier “autism”, when taken by a dominant discourse, the dimension of the human as a being traversed by language, becomes dispensable. It is in this context that we see emerging what resists to the knowledge of the Other and wich is imputed to the living being – the dimension of the subject as a pure effect of language. But, how to speak of the subject of the unconscious in a context whose essential characteristc seems to be non-alienation to the Other’s field? Is there a subject in autism? These are the questions that guide the investigation of this research. Based on a critique of the way in wich the phenomena in autism have been historically apprehended, a theoretical/bibliographic research in psychoanalysis was carried out, using the psychoanalytical method of listening, analysing and interpreting the work material. The general objective was to investigate the question of the subject’s existence in autism, driven by the political bias of this proposition. Through the dimension of suffering, we sought to support the thesis of the subject’s existence as an effect that would be constituted through hard and constant work in autism, operated in a way that is too unique and challenging for its traditional conception: the subject’s constitutive logic would not be contemplated in its entirety, but the hypothesis of its birth and constitution would still be sustainable, being able to be sent to a stage that goes from the real to possible forms of alienation to the Other’s discourse.